An Analysis of Classification and Clustering Techniques used in Data Mining - Vishakha D, Charhate; A Manjare, Poonam (International Journal of Computer Sciences and Engineering, 2015)
We live in a time where the need for data mining is prevalent for extracting knowledge and understanding patterns, given the vast amount of data being generated. Clustering is one of the many data mining functionalities which divide data into groups containing similar data objects Classification is a technique used for discovering classes of unknown data. Before applying any mining technique, irrelevant attributes needs to be filtered. Filtering is done using different feature selection techniques like wrapper, filter and embedded technique. This paper is an introductory paper on different techniques used for classification and clustering.